Peran Keluarga dalam Mendukung Kesejahteraan Anak Berkebutuhan Khusus (ABK) di SLB Kasih Ibu Dolok Masihul - Ade Rizky Anantya; Berlianti Berlianti; Hairani Siregar (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2025)
Children with special needs (ABK) often face various challenges that require extra attention and support from their families. This study aims to determine the role of families in supporting the welfare of ABK at SLB Kasih Ibu in Dolok Masihul District. The research method used is qualitative descriptive research. Data collection was conducted through interviews, observation, and documentation. There were nine informants in this study. The results showed that the family plays a role in improving the welfare of children with special needs through several main aspects, namely: family resilience, which includes physical, social, and psychological resilience, which is fulfilled through basic needs, religious values, communication, commitment, and emotional management. The family provides personal support in the form of information, emotional support, education, and daily assistance. Good family relationships with effective communication and positive reinforcement, as well as the lack of community capacity in serving children with special needs. The welfare of children with special needs is fulfilled through basic needs, care, nurturing, and guidance from their families. Families also play a role in meeting the basic needs of children with special needs and protecting them from violence, discrimination, and unfair treatment, thereby creating a safe and supportive environment for the optimal development of children with special needs..